Reimagining a future for game studies, from the ground up - Taylor, Nicholas T. (Eludamos: Journal for Computer Game Culture, 2023)
This article posits a future for game studies based on considering the ground—metaphorically and quite literally—upon which we play, produce, distribute, and work with games. Offering a critical consideration of the mobile game Temple Run inspired by both postcolonial and anticolonial scholarship, I explore some of the ways in which games transform our relations to land. This offers a multiscalar understanding of games and (in) place. From this perspective it becomes possible to understand how games are materially imbricated in some of our most urgent challenges—a central task for game studies, both present and future.